2012
DOI: 10.1016/j.clinbiochem.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of practices to reduce blood sample hemolysis in EDs: A laboratory medicine best practices systematic review and meta-analysis

Abstract: Use of new straight needle venipuncture instead of IV starts is effective at reducing hemolysis rates in EDs, and is recommended as an evidence-based best practice. The overall strength of evidence rating is high and the effect size is substantial. Unpublished studies made an important contribution to the body of evidence. When IV starts must be used, observed rates of hemolysis may be substantially reduced by placing the IV at the antecubital site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
59
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 21 publications
6
59
1
1
Order By: Relevance
“…5 This haemolysis rate is likely contributed to by collecting samples via an intravenous cannula, as is our local ED protocol, but is known to give higher rates of haemolysis compared to straight needle venipuncture. 6 The haemolysis in these samples may be attributable to the cannula itself, given that one previous study found no difference in haemolysis rates (at haemolysis index 0.8 or 1.2 g/L) in specimens collected through a cannula connector valve and those collected directly from the cannula. 7 In our study, samples were all collected via a cannula connector valve.…”
Section: Discussionmentioning
confidence: 99%
“…5 This haemolysis rate is likely contributed to by collecting samples via an intravenous cannula, as is our local ED protocol, but is known to give higher rates of haemolysis compared to straight needle venipuncture. 6 The haemolysis in these samples may be attributable to the cannula itself, given that one previous study found no difference in haemolysis rates (at haemolysis index 0.8 or 1.2 g/L) in specimens collected through a cannula connector valve and those collected directly from the cannula. 7 In our study, samples were all collected via a cannula connector valve.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic contrast enhanced MRI uses extravasation of low-molecular weight contrast agents along with repeated T1-weighted imaging to evaluate the degree of BBB disruption and has been used in human and animal models in a variety of applications from tumors to stroke [38][39][40][41]. Investigators using MRI with diffusion weighted imaging (DWI) technology have been able to identify temporal and regional differences in edema following TBI in rabbits.…”
Section: Clinical Measurement Of Bbb Permeabilitymentioning
confidence: 99%
“…Heyer and colleagues' systematic review on this topic has identified practices to reduce blood sample hemolysis in the ED setting with one particular intervention (i.e., straight needle venipuncture instead of intravenous (IV) catheters) being highly effective at reducing the hemolysis rate in this setting [2]. Overall, the authors assessed seven different interventions; of which there were no studies assessing the use of phlebotomist versus ED nurses/staff or the effect of tourniquet time and hemolysis; with two additional interventions (i.e., needle size and blood collection from IV catheters) having insufficient evidence [2].…”
mentioning
confidence: 98%
“…One particular hospital department where the presence of hemolysis may adversely affect laboratory results which in turn may have an immediate impact on patient care is the emergency department (ED) [2]. In addition to chemistry analytes that have critical values (i.e., potassium) where hemolysis will result in elevated concentrations regardless of the analytical method; other analytes (e.g., acetaminophen, salicylate, cardiac troponin) used in the ED setting may be affected based on the specific methodology and on the amount of hemolysis present [3][4][5][6][7][8].…”
mentioning
confidence: 99%